ENGLISH-RUSSIAN-UZBEK FALSE FRIENDS IN MARKETING AND MANAGEMENT TERMS - N. A. Mansurova (International Journal of Innovations in Engineering Research and Technology, 2021)
Nowadays, English is currently studied as a second language, a foreign language, or an international language at schools all around the world. While the two former concepts of English as a second or foreign language have been used for a long time, the latter concept of English as an international language is relevantly new.The role of false friends in English-Russian-Uzbek language in marketing and management spherewas mentionedin the article. False friends, also known as false cognates, are pairs of words which have a similar form and /or pronunciation but different meanings in two languages. The aim of this study is to raise awareness in avoiding misunderstanding, which English-Russian- Uzbek false friends cause inEnglish-medium intercultural communication. Some of the common English-Russian-Uzbek false friends in English-medium communicative situations have been identified and analyzed by the participation of teachers and learners.